Passive hip movement measurements related to dynamic motion during gait in hip osteoarthritis. Issue 10 (3rd March 2016) - Baker, Matt; Moreside, Janice; Wong, Ivan; Rutherford, Derek J.
ABSTRACT: Reduced sagittal plane range of motion (ROM) has been reported in individuals with hip osteoarthritis (OA) both during walking and passive testing. The purpose of this study was to determine if a relationship exists between hip extension ROM recorded during gait and passive hip extension ROM in individuals with moderate and severe hip OA, in comparison to an asymptomatic group. Sagittal plane hip ROM was calculated using skin surface marker trajectories captured during treadmill walking at self‐selected speed. Passive hip ROM was measured using standardized position and recording procedures with a goniometer. Sagittal plane extension, flexion, and overall ROM were measured dynamically and passively. A two‐way mixed model analysis of variance determined significant differences between groups and between passive and dynamic ROM ( α = 0.05). Pearson correlations determined relationships between passive and dynamic ROM. Significant group by ROM interactions were found for flexion and extension ROM ( p < 0.05). For extension, the severe OA group had less dynamic and passive ROM compared to the other groups and greater passive than dynamic ROM ( p < 0.05). For flexion, significant differences in passive ROM existed between all three groups ( p < 0.05) whereas no differences were found for dynamic flexion ( p < 0.05). Significant correlations between dynamic and passive hip extension were found in the moderate ( r = 0.596) and severe OA ( r = 0.586) groups, and no correlation was found in the asymptomatic group ( r = 0.139). Passive ROM explains variance in dynamic ROM measurements obtained during gait in individuals with moderate and severe hip OA which have implications for the design of treatment strategies targeting walking pathomechanics. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1790–1797, 2016.